Strategi Pemasaran Untuk Meningkatkan Jumlah Pelanggan Pada Hotel Bukit Serelo Lahat - Novriansyah (Jurnal Manajemen dan Bisnis, 2020)
Nowadays the hospitality business is growing in Indonesia. Hotel Bukut Serelo is a party that also plays an active role in improving the world of hospitality. For that Hotel Bukut Serelo must arrange and implement a strategy in marketing and also improve the weaknesses that exist. If Hotel Bukut Serelo implement marketing strategy then there will be an increase in the number of occupancy. This study aims to determine the best marketing strategy to increase the number of customers of Hotel Bukut Serelo Lahat by conducting SWOT analysis. The results of SWOT analysis produce marketing strategies such as: Social media usage for promotion, Offer tourism package in cooperation with local people, Offer promotions on special days such as Lahat's birthday, Recruit reliable staff to fill the position of marketing manager, Add new menu, Adding new parking area, Improving facilities, Providing training for employees, Cooperating with travel agents and online travel agents, and implementing reward and punishment system for employees.